Corn and sorghum ground or rehydrated and ensiled in feedlot cattle diets - Laissa Araujo Guimarães; Severino Delmar Junqueira Villela; Jane Maria Bertocco Ezequiel; Paulo Gustavo Macedo de Almeida Martins; Patrícia Monteiro Costa; Fernando de Paula Leonel; Cláudio Manoel Teixeira Vitor; Josimari Regina Paschoaloto (Revista Brasileira de Zootecnia)
ABSTRACT This study aimed to evaluate the effects of dried or rehydrated corn and sorghum grains on nutrient intake, performance, and economic analysis in high-grain diets (30:70) of Nellore bulls finished in a feedlot system. The experiment was completely randomized and replicated four times (two animals/pen), in which 32 Nellore bulls with an initial body weight (IBW) of 324.8±4.42 kg were fed in 16 pens according to the following treatments: rehydrated corn silage (RCS), rehydrated sorghum silage, dry corn grain, and dry sorghum grain. Dry matter intake, IBW, and final body weight did not differ among treatments, although diets with RCS and ground corn grain had better daily weight gain (1.60 and 1.52 kg/head/day, respectively). Rehydrated corn silage allowed lower daily costs (US$ 2.12/day) in relation to ground corn grain (US$ 2.14/day). Rehydrated sorghum grain silage is recommended instead of dry sorghum grain in beef cattle diets since it provides greater net margin, without affecting the average daily gain. Similarly, the rehydrated corn grain diet presents greater technical and economic efficiency than dry sorghum or rehydrated sorghum silage, indicating greater system profitability.